Influence of Biological Factors, i.e., Blood Groups on Emotional Intelligence on the Performance of Pre-Service Teachers - R.S.S. Nehru (International Journal of Psychosocial Rehabilitation, 2020)
Emotional Intelligence (E.I.) alludes to the capacity to see, control, and assess feelings. A few analysts recommend that Emotional Intelligence can be learned and fortified, while others guarantee it is an inalienable trademark. There are numerous potential meanings of Emotional Intelligence that can be found on the Internet and in the well known press and books. A reasonable and experimentally helpful sense of Emotional Intelligence, in any case, is unmistakable because it pays attention to the term’s feeling, knowledge, and behavior. Emotional Intelligence helps teachers face certain stressful situations in which their actions can impact their learning and wellbeing. It also helps them deal with the new challenges that come with problematic groups of students, crowded classrooms, or a lack of motivation. Emotions influenced by biological factors like Blood Pressure, Suger levels, and even Blood groups, etc.. So this study, the investigator gathers the information from pre-Service teachers (D.Ed, B.Ed, and M.Ed). Along with biological factors(i,e., Blood Groups) influence Academic Performance with how to identify and control and modify the behavior in the teacher and teaching profession. This study conducted among the Teacher Trainees of colleges of education in Andhra Pradesh (India).